(untitled) (Research, Society and Development, 2021)
The objective of this work was to characterize the containment systems in the microregions of Cametá, Guamá, Tomé-Açu, Bragantina and Paragominas in the state of Pará. For this, 20 producers were interviewed using a semi-structured script containing open and closed questions by qualitative and quantitative approaches. The selection of the sample was based on the snowball technique and the application of the information was evaluated in August and September 2019. The interview script contained 101 questions aimed at identifying the owner, general characterization of the property, characterization of the production unit considering animals and the structure of the production system. The data obtained were obtained in Excel spreadsheets and processed with IBM SPSS Statistics software version 22.0SPSS to perform descriptive statistical analyzes and inferences compared with the literature. We conclude that the exploitation of the containment system in the region is recent and has grown over the past 10 years. The producers have a medium to high level of education, which facilitates access to technology and technical assistance that was observed in all cases. In most properties the activity is carried out in the dry season to maintain weight gain as the main objective. In general, there is an adequate structure to carry out activities, with the inclusion of improved genetics in herds and few cases of disease mortality in the terminal phase of beef cattle. Meat quality programs in slaughterhouses can encourage an increase in the use of technology in the region.